PEMBERDAYAAN UMKM DAN LEMBAGA KEUANGAN SYARIAH MELALUI PRINSIP BAGI HASIL - Bhakti, Rizki Tri Anugrah; Bakri, Mochammad; Hamidah, Siti (De Jure: Jurnal Hukum dan Syari'ah, 2013)
This article describes the micro, small and medium enterprises (SMEs), which has high ability  to  absorb  labor  market,  as  many  as  97.3%  from  the  total  labor  force  working. However,  the  role  of  micro,  small  and  medium  enterprises  (SMEs)  in  the  reality  have difficulties in some factors, one of the factor is capital issues. This is where Syariah financial institution  with  the  profit  sharing  principal  to  be  expected  become  ideal  solution,  this because on the financing use the profit sharing principal. Observing phenomenon as above it is necessary to have assessment on few point area, first, implementation of financing on Syariah financial institution in the Malang City perceived become ideal solutions. Second, the factors which become the barrier on implementation of financing on Syariah financial institution in Malang City. Third; the right solution to overcome the barrier factors on the implementation at Shariah financial institution in Malang City concerning exact profit sharing principal. Artikel ini membahas tentang kemampuan usaha mikro, kecil dan menengah (UMKM) dalam menyerap tenaga kerja di Indonesia yang cukup besar, yaitu sebanyak 97,3% dari total angkatan kerja yang bekerja. Namun peran tersebut dalam kenyataannya terkendala oleh beberapa hal, diantaranya permasalahan modal. Disinilah peran Lembaga Keuangan Syari’ah dengan pembiayaan berprinsip bagi hasil sangat diharapkan. Mengamati fenomena yang demikian maka perlu dikaji mengenai beberapa hal; pertama, pelaksanaan pembiayaan pada Lembaga Keuangan Syari’ah di kota Malang yang dirasa ideal bagi usaha mikro, kecil dan menengah (UMKM). Kedua, faktor-faktor penghambat pelaksanaan pembiayaan pada Lembaga Keuangan Syari’ah di Kota Malang berkenaan dengan prinsip bagi hasil, dan ketiga,  solusi  untuk  mengatasi  faktor-faktor  penghambat  pelaksanaan  pembiayaan  pada Lembaga Keuangan Syari’ah di Kota Malang berkenaan dengan prinsip bagi hasil yang ideal tersebut.